1991
DOI: 10.1016/0026-0495(91)90051-w
|View full text |Cite
|
Sign up to set email alerts
|

Plasma levels of lathosterol and phytosterols in relation to age, sex, anthropometric parameters, plasma lipids, and apolipoprotein E phenotype, in 160 Dutch families

Abstract: In this study, the relation of plasma levels of lathosterol (an indicator of whole body cholesterol synthesis) and plant sterols (indicator of cholesterol absorption) with age, sex, weight, height, plasma lipids, and lipoproteins, and with apolipoprotein (apo) E phenotype, was investigated in a group of 160 nuclear families consisting of twins living with their parents. Lathosterol was higher in fathers than in mothers, but not different between boys and girls. In each of these four groups, there was a strong … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
37
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 20 publications
7
37
2
Order By: Relevance
“…Serum plant sterol concentrations were analysed for all subjects, red blood cell plant sterol concentrations were analyzed in 23 randomly selected subjects consuming control spread and 23 randomly selected subjects consuming plant sterol esters spread. Blood samples and washed red blood cells were saponified and extracted and separated by capillary gas -liquid chromatography (Kempen et al, 1991) using epicoprostanol as an internal standard (CV ¼ 10%)…”
Section: Laboratory Analysesmentioning
confidence: 99%
“…Serum plant sterol concentrations were analysed for all subjects, red blood cell plant sterol concentrations were analyzed in 23 randomly selected subjects consuming control spread and 23 randomly selected subjects consuming plant sterol esters spread. Blood samples and washed red blood cells were saponified and extracted and separated by capillary gas -liquid chromatography (Kempen et al, 1991) using epicoprostanol as an internal standard (CV ¼ 10%)…”
Section: Laboratory Analysesmentioning
confidence: 99%
“…Despite the fact that most previous studies confirm the hypolipidemic effect of PS, it is not so clear whether this (Kempen et al, 1991;Geelen et al, 2002;Ishiwata et al, 2002;Lottenberg et al, 2002;Plat and Mensink, 2002;Tammi et al, 2002), one recent report concluded that PS therapy was of little value for E4 subjects with hypercholesterolemia owing to the lack of significant benefits in relation to TC and LDLc concentrations (SanchezMuñiz et al, 2009). Our results are in accordance with those of previous studies in which PS therapy was not influenced by Apo E genotype.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are in accordance with those of previous studies in which PS therapy was not influenced by Apo E genotype. Among these studies, several were carried out in normocholesterolemic subjects (Kempen et al, 1991;Geelen et al, 2002;Ishiwata et al, 2002;Plat and Mensink, 2002;Tammi et al, 2002) and others were performed in a hypercholesterolemic population (Lottenberg et al, 2002;Sanchez-Muñiz et al, 2009) with different doses and different types of PS (free sterols and stanols or stanol esters).…”
Section: Discussionmentioning
confidence: 99%
“…Plasma was immediately separated from the cells and stored at -20º Celsius until further use. Concentrations of lathosterol and plant sterols were measured with gas chromatography (for details see Kempen et al, 1991).…”
Section: Methodsmentioning
confidence: 99%